POTENSI TERSEMBUNYI KEKAYAAN "ARSTEKTUR HERITAGE" DI KOTA PEKALONGAN - Sri Puji Astuti (Jurnal Dimensi Seni Rupa dan Desain, 2007)
AbstractAs every Indonesians know, Pekalongan is the one of batik's Indonesian producers. The batik of Pekalongan has a special charateris tic, therefore this makes the Pekalongan's batik famous in all over the world. But, this is not such the only one cultural product in Pekalongan. Based mi the history background. Pekalongan was a big harbour town in past, so that many merchants in over the world came to this town for trading. In the period of Dutch colonialist, Many government buildings had built by Dutch. Dutch government buildings in Pekahmgan as we know as well today as heritage architectures. Dutch heritages architectures in Pekalongmt not just government buildings, there are also public buildings and residences. But, there is no enough attention from us, especially Pemerintah Kota Pekalongan, that the heritage architectures in Pekalongan have a hidden potential as a cultural tourism. By reading this article there will be a new awareness of us about one of our cultural products, especially architecture. This article also gives the image of Dutch heritages architectures in Jakarta and Malang, as a comparison.AbstrakSetiap orang Indonesia pasti tahu bahwa Pekalongan adalah salah satu kota penghasil batik di Indonesia. Batik Pekalongan memiliki ciri khusus, hal ini menjaciikan Batik Pekalongan terkenal di seluruh dunia. Tetapi batik hukanlah satu-satunya produk budaya yang ada di Pekalongan. Berdasar latar belakang sejarahnya ciahulu Pekalongan adalah sebuah kota pelabuhan besar sehingga banyak pedagang di seluruh dunia melakukan perdagangan di kota tersebut. Dalam masa penjajahan Belanda, banyak gedung pemerintahan yang clibangun oleh Belanda pada masa itu. Bangunan-bangunan pemerintahan Belanda tersebut sekarang kita kenal sebagai arsitektur heritage. Arsitektur heritage di Pekalongan tidak hanya berupa gedung-gedung pernerintahan, tetapi juga gedung-gedung